Post-War Homes, 1943 (pg. 1) (1943)
1943 1939-1945 "Post-War Homes, 1943 (pg. 1)" [HFR0108a], 1943 In 1943, the Standing Joint Committee of Working Women's Organisations published this survey of its women members' preferences for the design, building and equipment of post-war housing.